Meningkatkan Kemampuan Kognitif Anak pada Pembelajaran Sains Melalui Metode Eksperimen - Fauziah, Zulfa; Yulianingsih, Yuyun; Syamiyah, Syamiyah (JAPRA (Jurnal Pendidikan Raudhatul Athfal), 2019)
This study aims to improve children’s cognitive abilities in science learning through experimental methods in group B. The study used the mixed methods approach. This type of research is collaborative classroom action research. Research subjects in group B. Techniques for collecting data through observation, interviews and documentation. Data analysis techniques were carried out in qualitative descriptive and quantitative. The results showed that before the experimental method was applied it was obtained an average of 39,24% with very few criteria. After the application of the experimental method, children’s cognitive abilities in science learning have increased every cycle. This can be seen from the activities of teachers in the first cycle obtained an average of 70% with sufficient criteria and in the second cycle obtained an average of 90% with very good criteria, while the activities of children in the first cycle obtained an average of 65,39% with sufficient criteria and in the second cycle obtained an average of 84,62% with good criteria. In addition, children’s cognitive abilities in science learning in the first cycle obtained an average of 54 with less criteria an in the second cycle obtained an average of 76,04 with good criteria. Thus the application of experimental methods can improve children’s cognitive abilities in science learning in group B.